2019
DOI: 10.1177/0025802419830882
|View full text |Cite
|
Sign up to set email alerts
|

Police detentions of ‘mentally disordered persons’: A multi-method investigation of section 136 use in Sussex

Abstract: This research was conducted in response to governmental and public concern regarding the escalating use of section 136 of the Mental Health Act (1983) nationally and of the excessive use of police custody as a place of safety in Sussex in particular. A retrospective analysis of all detentions in Sussex during 2012 was combined with qualitative data from 37 people with lived experience of detention, as well as police, National Health Service (NHS) and allied staff and volunteers. Predominantly, police used s136… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(108 citation statements)
references
References 14 publications
2
46
0
Order By: Relevance
“…This study has taken a multifactorial approach to Many of those detained more than once were males who were subject to two detentions, suggesting this group may be representative of the wider cohort of people detained under S136, for whom a period of crisis culminates in police intervention that can then prompt appropriate help-seeking and access to support services, albeit through a harrowing experience of being detained [13,46]. However, this research has confirmed that those subject to the highest numbers of police Mental Health Act detentions are almost exclusively female.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has taken a multifactorial approach to Many of those detained more than once were males who were subject to two detentions, suggesting this group may be representative of the wider cohort of people detained under S136, for whom a period of crisis culminates in police intervention that can then prompt appropriate help-seeking and access to support services, albeit through a harrowing experience of being detained [13,46]. However, this research has confirmed that those subject to the highest numbers of police Mental Health Act detentions are almost exclusively female.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates place between 55% and 81% of detentions as being linked to concerns about the detained person's risk to their own life rather than to the threat of harming others [11,12]. A recent comprehensive study investigating the use of S136 in the adjacent South East England counties of East and West Sussex revealed many important elements involved in the historically high rates of detention seen within that area [13]. In addition to confirming the high incidence of detentions related to suicide prevention, the findings indicated one issue requiring further investigation was that a small number of people had been detained multiple times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2325 In contrast to the idea that policing is solely about law enforcement, Bendelow and colleagues found that officers took seriously a pastoral concern with public protection, especially in cases of threatened suicide and/or self-harm – expressions of mental distress which recent studies have found to predominate amongst s136 detainees. 2327 Other recent research into police attitudes, notably that of Thomas and Forrester-Jones, lends some support to Bendelow’s ‘pastoral’ perspective by suggesting that it interacts with a ‘risk-averse culture’ within the police that itself contributed to the s136 rise. 28 The hypothesis here is that as mental-health issues became increasingly part of the police’s ‘core business’, so an awareness of suicide risk and pastoral concerns combined together to increase the use of s136 and the removal of the detainee to the increasingly available HBPOS rather than to a police cell.…”
Section: Cultural Factorsmentioning
confidence: 99%
“…Self-harm may also be relevant for a longer-term causal analysis of the s136 rise in the aftermath of the GFC and austerity in two ways: first because several studies have indicated that a significant reason for the police’s use of s136 occurs when the detainee is at risk of self-harm and/or suicide, including the already cited work of Thomas and Forrester-Jones; and second because Bendelow’s research emphasised how the decision making of police officers was influenced by their non-medical classifications of mental distress. 24,25,28 ‘Detentions were coded as “Suicidal”’, Bendelow and colleagues observed, ‘if the records had stated the person was detained because of concerns that they intended to end their life, had taken an overdose etc.’. 24 This is significant for what Loughran called the ‘threshold’ problem: over time, police attitudes have reduced the threshold which needs to be met for s136 to be implemented, and this reduction seems to be related to their increasing awareness of suicidal and self-harming behaviour.…”
Section: Economic Factorsmentioning
confidence: 99%